Platelet‐rich plasma affects gap junctional features in myofibroblasts in vitro via vascular endothelial growth factor (VEGF)‐A/VEGF receptor. Issue 2 (4th January 2022) - Sassoli, Chiara; Garella, Rachele; Chellini, Flaminia; Tani, Alessia; Pavan, Paola; Bambi, Franco; Zecchi‐Orlandini, Sandra; Squecco, Roberta
Abstract : New Findings: What is the central question of this study? It is a challenge to discover effective therapies for fibrosis. Increasing evidence supports the antifibrotic potential of platelet‐rich plasma (PRP) as a source of bioactive molecules, such as vascular endothelial growth factor (VEGF)‐A. However, the effects and mechanisms of action of PRP need to be clarified. What is the main finding and its importance? This report clarifies the mechanisms mediating the antifibrotic action of PRP, strengthening the role of VEGF‐A/VEGF receptor, and identifies gap junction currents and connexin 43 as novel targets of this pathway in the fibroblast‐to‐myofibroblast transition induced by the transforming growth factor‐β1. Abstract: Despite increasing experimental evidence, the antifibrotic potential of platelet‐rich plasma (PRP) remains controversial, and its mechanisms of action are not fully clarified. This short report extends our previous research on the capability of PRP to prevent the in vitro differentiation of fibroblasts toward myofibroblasts, the key effectors of fibrosis, induced by the profibrotic agent transforming growth factor‐β1 (TGF‐β1). In particular, we focused on the involvement of signalling mediated by vascular endothelial growth factor (VEGF)‐A/VEGF receptor (VEGFR) in the PRP‐induced fibroblast response, highlighting gap junction features. Electrophysiological and morphological analyses revealed that PRP hindered morphofunctional differentiation of both murine NIH/3T3 and human primary adult skin fibroblasts toward myofibroblasts as judged by the analysis of membrane phenomena, α‐smooth muscle actin and vinculin expression and cell morphology. Neutralization of VEGF‐A by blocking antibodies or pharmacological inhibition of VEGFR by KRN633 in TGF‐β1‐treated fibroblasts prevented the PRP‐promoted effects, such as the reduction of voltage‐dependent transjunctional currents in cell pairs and a decreased expression of connexin 43, the typical connexin isoform forming voltage‐dependent connexons. The role of VEGF‐A in inhibiting these events was confirmed by treating TGF‐β1‐stimulated fibroblasts with soluble VEGF‐A. The results obtained when cells were differentiated using KRN633 alone suggest an antagonistic cross‐talk between TGF‐β1 and VEGFR. In conclusion, this study identifies, for the first time, gap junction currents as crucial targets in the VEGF‐A/VEGFR‐mediated antifibrotic pathway and provides new insights into mechanisms behind the action of PRP in preventing differentiation of fibroblasts to myofibroblasts.